Implementation and Operational Research: Evaluating Outcomes of Patients Lost to Follow-up in a Large Comprehensive Care Treatment Program in Western Kenya. (1st April 2015) - Rachlis, Beth; Ochieng, Daniel; Geng, Elvin; Rotich, Elyne; Ochieng, Vincent; Maritim, Beryl; Ndege, Samson; Naanyu, Violet; Martin, Jeffrey N.; Keter, Alfred; Ayuo, Paul; Diero, Lameck; et al.
Abstract : Background: Academic Model Providing Access To Healthcare (AMPATH) program provides comprehensive HIV care and treatment services. Approximately, 30% of patients have become lost to follow-up (LTFU). We sought to actively trace and identify outcomes for a sample of these patients. Methods: LTFU was defined as missing a scheduled visit by ≥3 months. A randomly selected sample of 17% of patients identified as LTFU between January 2009 and June 2011 was generated, with sample stratification on age, antiretroviral therapy (ART) status at last visit, and facility. Chart reviews were conducted followed by active tracing. Tracing was completed by trained HIV-positive outreach workers July 2011 to February 2012. Outcomes were compared between adults and children and by ART status. Results: Of 14, 811 LTFU patients, 2540 were randomly selected for tracing (2179 adults, 1071 on ART). The chart reviews indicated that 326 (12.8%) patients were not actually LTFU. Outcomes for 71% of sampled patients were determined including 85% of those physically traced. Of those with known outcomes, 21% had died, whereas 29% had disengaged from care for various reasons. The remaining patients had moved away (n = 458, 25%) or were still receiving HIV care (n = 443 total, 25%). Conclusions: Our findings demonstrate the feasibility of a large-scale sampling-based approach. A significant proportion of patients were found not to be LTFU, and further, high numbers of patients who were LTFU could not be located. Over a quarter of patients disengaged from care for various reasons including access challenges and familial influences.